QUALITY OF HEALTH SERVICES AND PATIENT SATISFACTION OF NATIONAL HEALTH INSURANCE PARTICIPANTS AT WIRE HEALTH CENTER - Adibah Enggar; Muhammad Sudrajad (International Nutrition and Health Administrations Journal, 2025)
The community health center (Puskesmas) is one of the many stakeholders involved in the implementation of the national health insurance program, which aims to provide health protection to participants with the goal of maintaining health and safeguarding to meet basic health needs. Patient satisfaction is influenced by the quality of health services. This research aims to explore between the quality of health services and patient satisfaction among National Health Insurance participants at the Wire Community Health Center. This type of research is quantitative with a cross-sectional approach at the Wire Community Health Center. The sample in this study consists of 108 individuals selected using probability sampling techniques with simple random sampling method. Data collection was conducted using a questionnaire that covered aspects of healthcare service quality. The results of the study, after being analyzed using Spearman with a significance level of a = < 0.05, showed a value of r = 0.000 < 0.05, with a correlation coefficient of r = 0.048, which means the strength of the relationship between the two variables is categorized as strong. Based on the analysis of the data, it can be concluded that there is a relationship between the quality of health services and patient satisfaction among national health insurance participants at the Wire Community Health Center. The quality of service at the Wire Community Health Center is good, and the majority of national health insurance patients are satisfied with the services provided.